Community organizing practices in a globalizing era: Building power for health equity at the community level. (January 2014) - Speer, Paul W; Tesdahl, Eric A; Ayers, Jeanne F
In the postindustrial era, global economic processes have constrained the ability of local agencies, service providers, and civic groups to respond to systemic challenges in public health. Community health psychology can benefit by focusing on interventions through mediating structures that develop innovative methods of leveraging power in the context of globalizing economic forces. Promising methods include careful analysis of power within targeted policy domains and developing strategic alliances with others, so as to exercise social power to affect policy change. The case of ISAIAH, an organizing group based in Minnesota, illustrates innovative avenues for intervention in the context of globalization.